2015
DOI: 10.1007/s13524-015-0371-8
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Variations in Immigrant Poverty Exit and Female Employment: The Missing Link

Abstract: Despite widespread interest in poverty among recent immigrants and female immigrant employment, research on the link between the two is limited. This study evaluates the effect of recently arrived immigrant women’s employment on the exit from family poverty and considers the implications for ethnic differences in poverty exit. It uses the bivariate probit model and the Fairlie decomposition technique to analyze data from the Longitudinal Survey of Immigrants to Canada (LSIC), a nationally representative survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…Overall, behavioralists contend that poverty is high in these contexts due to high prevalences of risks and counter-productive behaviors (Cruz and Ahmed 2018;Kaida 2015;Ku et al 2018;Milazzo and Van de Walle 2015). Thus they conclude that to reduce poverty the prevalence of risks must be reduced (AEI-Brookings 2015;McLanahan 2009).…”
Section: Behavioral Explainations Of Povertymentioning
confidence: 99%
“…Overall, behavioralists contend that poverty is high in these contexts due to high prevalences of risks and counter-productive behaviors (Cruz and Ahmed 2018;Kaida 2015;Ku et al 2018;Milazzo and Van de Walle 2015). Thus they conclude that to reduce poverty the prevalence of risks must be reduced (AEI-Brookings 2015;McLanahan 2009).…”
Section: Behavioral Explainations Of Povertymentioning
confidence: 99%
“…Many newcomer women disclosed that they could not afford healthy food and necessary medications, and were unable to qualify for extended health benefits, including access to paid sick days (Premji & Shakya, 2017). Another study conducted by Kaida (2015) found that 60 percent of European-born newcomer women exited poverty after four years in Canada, while only 22 percent of Arab women and 28 percent of West Asian women were able to do so. Race and ethnicity clearly matter when considering the unemployment/ underemployment trajectories of newcomer women.…”
Section: Challenges Encountered By Newcomersmentioning
confidence: 99%
“…Immigration status. As compared with their US-born counterparts, low-income immigrant householders are less likely to be employed and less likely to become financially stable (Kaida, 2015;Waters & Eschbach, 1995). In this research, immigration status captures whether study participants were foreign-born or US-born.…”
Section: Samplementioning
confidence: 99%